Factors associated with breastfeeding maintenance for 12 months or more: a systematic review - Géssica S. Santana; Elsa Regina J. Giugliani; Tatiana de O. Vieira; Graciete O. Vieira
Abstract Objective Synthesize the information about the factors associated with maintenance of breastfeeding for 12 months or more. Data source A systematic review was conducted in the Pubmed/Medline, Scielo, and Lilacs databases, including articles published in Portuguese or English since 2004 on the factors associated with breastfeeding maintenance for at least 12 months; review articles and those with qualitative design were excluded. The factors were organized into four levels, according to the chronological proximity to the outcome: distal, distal intermediate, proximal intermediate, and proximal; nationality and place/area of residence were considered contextual factors. Summary of data 1174 articles were identified, of which 19 were included in this review, comprising seven cohort studies and 12 cross-sectional studies. A total of 39 of the 75 assessed factors were associated with the outcome at least once. The factors with the highest percentages of associations with maintenance of breastfeeding for 12 months or more, considering the number of times they were tested were: children whose parents are the caregivers (100%), none type of maternal exposure to smoke (54%), children and/or parents are immigrants/foreigners (50%), live in urban areas (42.9%), older maternal age (40%), married women (37.5%), higher level of maternal education (31.3%), greater parity (30.8%), and lower income (30%). Conclusions The maintenance of breastfeeding for 12 months or more is associated with multiple factors, emphasizing the contextual factors and those related to some maternal sociodemographic characteristics. Associations differ in effect and magnitude between the different populations studied.